Low-loss Polymer Optical Components and Cladding Interferometric Devices Inscribed Using Femtosecond Laser Inscription - Theodosiou, Antreas; Ioannou, Andreas; Stassis, Andreas; Kalli, Kyriacos (My University, 2019)
We present the development of low-loss polymer optical fiber components and interferometric devices in perfluorinated multimode fibers like CYTOP and silica fibers, respectively. This includes the inscription of usable fiber Bragg gratings, chirped gratings and Fabry-Perot cavities in multimode gradient index fiber using a femtosecond laser inscription. We present the successful demonstration of interferometric devices such as Mach-Zehnder filters and Fabry-Perot cavities inscribed in the cladding of a single mode silica optical fiber. The advantages of these particular progressive sensors are discussed.
Keywords: Cladding devices; Femtosecond lasers; Fiber Bragg gratings; Monolithic interferometric devices; Polymer sensors